1998
DOI: 10.1210/jc.83.12.4474
|View full text |Cite
|
Sign up to set email alerts
|

Deficient 17 -Hydroxysteroid Dehydrogenase Type 2 Expression in Endometriosis: Failure to Metabolize 17 -Estradiol

Abstract: Aberrant aromatase expression in stromal cells of endometriosis gives rise to conversion of circulating androstenedione to estrone in this tissue, whereas aromatase expression is absent in the eutopic endometrium. In this study, we initially demonstrated by Northern blotting transcripts of the reductive 17beta-hydroxysteroid dehydrogenase (17betaHSD) type 1, which catalyzes the conversion of estrone to 17beta-estradiol, in both eutopic endometrium and endometriosis. Thus, it follows that the product of the aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
2
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 0 publications
6
126
2
5
Order By: Relevance
“…The type 1 isozyme was the first 17 -HSD isozyme identified in endometrium (Mäentausta et al 1991). The importance of its function in this tissue is controversial, because it is expressed at very low levels compared with the other isozymes (Milewich et al 1989, Casey et al 1994, Zeitoun et al 1998. This was confirmed in our study, since the expression of both 17 -HSD types 2 and 4 is much higher in human endometrial tissue and in cell lines.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The type 1 isozyme was the first 17 -HSD isozyme identified in endometrium (Mäentausta et al 1991). The importance of its function in this tissue is controversial, because it is expressed at very low levels compared with the other isozymes (Milewich et al 1989, Casey et al 1994, Zeitoun et al 1998. This was confirmed in our study, since the expression of both 17 -HSD types 2 and 4 is much higher in human endometrial tissue and in cell lines.…”
Section: Discussionsupporting
confidence: 81%
“…Oxidative 17 -HSD activity in the uterus has been assigned to two isozymes: 17 -HSD2 (in the human: Casey et al 1994, Mustonen et al 1998, Zeitoun et al 1998 or 17 -HSD4 (up to now shown only in porcine uterus: Adamski et al 1992, Husen et al 1994. Both belong to the gene family of short chain alcohol dehydrogenases, but they share only 16·4% amino acid identity (Labrie et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Также к факторам высокого риска ма-лигнизации можно отнести низкую чувствительность эндометриоидных гетеротопий к гормонотерапии, так называемый атипический эндометриоз [13]. Ряд ав-торов обращают внимание на влияние внешних фак-торов окружающей среды, а именно ее загрязнение, наличие полихлорированных бифенилов и диоксинов [14]. Таким образом, под действием многих факторов развивается атипический эндометриоз, для которого характерны выраженные адгезивные и миграционные свойства, изменения в метаболизме эстрогенов и гор-мональных рецепторах, ферментная недостаточность с накоплением агрессивных метаболитов стероидов.…”
Section: обзорные статьиunclassified
“…[1] E2 is known to play a crucial role in the development and progression of several estrogen dependent diseases (EDD). [2][3][4][5] Increased E2/E1 ratios as well as elevated 17β-HSD1 mRNA levels are indicators of the involvement of 17β-HSD1 in breast cancer [6,7], ovarian tumor [8], endometriosis [9], endometrial hyperplasia [10] and other EDD [11]. Consequently, the selective inhibition of this enzyme is considered as a valuable treatment option.…”
Section: Introductionmentioning
confidence: 99%